Performance Analysis of APILL at the Intersection of Jl. Pemuda Timur - Jl. Ngampel and Jl. Lisman - Jl. Veteran, Bojonegoro Regency: Analisis Kinerja Simpang APILL Pada Simpang Empat Jl. Pemuda Timur - Jl. Ngampel Dan Jl. Lisman – Jl. Veteran Kabupaten Bojonegoro - Rahmawati, Alfia Nur Rahmawati; Yulis Widhiastuti; Andy Yanuar Putra Riyadi (Universitas Negeri Surabaya, 2025)
An intersections are areas where two or more roads meet and often cause traffic conflicts that can lead to congestion and accidents, especially in locations near crowded centers. With the development of cities such as Bojonegoro, which has industrial, tourism, and educational activities, the volume of vehicles at certain intersections has increased rapidly, especially at certain hours. One of the busy intersections in Bojonegoro is the Four-Way, which requires effective traffic management through the use of traffic signal devices (APILL). However, the physical conditions of this intersection, such as unclear left-turn signs and limited visibility, increase the risk of vehicle conflicts. These conditions prompted the idea to conduct research analyzing the performance of the traffic signal system at the Four-Way Intersection of Jl. Lisman, Jl. Veteran, Jl. Ngampel, and Jl. Pemuda Timur in Bojonegoro using the PKJI 2023 method. This study aims to analyze the performance of the APILL at this intersection and identify alternative phases required if the APILL performance is inadequate, with the hope of improving understanding of traffic performance at this intersection, evaluating road service levels from a delay perspective, and providing useful data for relevant parties and future